The role of cultural differences in customer retention: Evidence from the high-contact service industry - Fam, K. S.; Cheng, Boon Liat *; Cham, Tat Huei; Tan, C. Y. (Sage, 2021)
Current tourism landscape and dynamism of the business environment have increased market competitiveness in the high-contact service industry. Hotel operators must now pay greater heed to customer retention by exploring ways to improve customer engagement and experience. Toward this end, this study aimed to examine the interplays between relationship marketing, perceived service quality, corporate image, customer satisfaction, and customer loyalty, as well as the moderating effect of cultural difference between Asian and Western tourists. Using a questionnaire, data were collected from 400 international tourists and analyzed with the structural equation modeling technique. While the direct relationships pertaining the variables of interest were found to be significant, Asian tourists appeared to hold stricter standards in employee–customer interactions and satisfaction-based loyalty than Western tourists. Discussion and implications are provided to promote the development of fruitful hotel–customer relationships in this industry with a heightened customer orientation.